Analisis Pesan Dakwah Ustadz Agam Fachrul di Media Sosial - Maufiratun Nisa (Meyarsa: Jurnal Ilmu Komunikasi dan Dakwah, 2025)
The increasing phenomenon of anxiety and stress, especially among the younger generation, poses a serious challenge in modern life. In this context, da'wah (Islamic preaching) as a medium of spiritual communication plays a crucial role in providing enlightenment and inner peace. This study aims to analyze the da'wah message of Ustadz Agam in the YouTube channel Ismuhu Yahya TV, "Episode of Tranquility." The research focuses on: 1) a description of Ustadz Agam's da'wah message and 2) Ustadz Agam Fachrul's da'wah message about "tranquility" uploaded to the YouTube channel Ismuhu Yahya TV. This research is a library research study with a qualitative approach, using the content analysis method (Harold D. Laswell) to systematically analyze the content of the da'wah message. The results indicate that the structure of the da'wah message consists of three main parts: the introduction, the body, and the conclusion. The messages of da'wah found include: the importance of the power of prayer, appreciating every moment, facing sadness with faith, overcoming sadness and weakness, seeking peace through worship, the importance of prioritizing obedience to Allah and His Messenger, the virtue of the power of istighfar, always relying on Allah SWT in any situation, the importance of prioritizing tawakkul (trust), increasing the capacity of the soul when facing problems, and always being grateful to parents.